Effect of nanocrystallinity on lattice dynamics in Bi2Te3 based thermoelectrics. Issue 1 (12th November 2014) - Klobes, B.; Bessas, D.; Juranyi, F.; Görlitz, H.; Pacheco, V.; Hermann, R. P.
<x xml:space="preserve">Abstract</x> The lattice dynamics in as‐cast and nanocrystalline thermoelectric Bi2Te3 based p‐type and n‐type material were investigated using inelastic neutron scattering. Generalized densities of phonon states show substantial agreement between the lattice dynamics in as‐cast samples and previous studies. The lattice dynamics in the nanocrystalline materials differ significantly from its as‐cast counterparts in the acoustic phonon regime. In nanocrystalline p‐type and n‐type compounds, the average acoustic phonon group velocity was found to be reduced to 80(5)% and 95(2)% of the value in as‐cast material. It is argued that point‐defect and strain contrast scattering may play an important role for the understanding of lattice thermal conductivity in (nanocrystalline) Bi2Te3 based thermoelectrics beside the observed decrease of sound velocity. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)